Aplication of Multicriteria Decision Making (MCDM) Method by Weighting Technic Using in Identifying and Designing Marine Protected Area in North Luwu, South Sulawesi Province - Chair Rani, 1; M. Natsir Nessa, 2; Ahmad Faisal, 3; M. Farid Samawi, 4 (Journal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
This study,in 2012, has successfully formulated with the MCDM for each allocation of space in KKPD allotment (core areas, sustainable fisheries zone, used zone, and other zones). This study aims to identify and map the biophysical conditions and the potential of coastal and marine natural resources in marine conservation area candidate, North Luwu Regency; to identify the areas suitable for the KKPD based on weighting technique with the MCDM method; and to evaluate potential candidates for marine protected areas in the coastal region. This study used a  survey method to perform in situ measurements of physico- chemical parameters, conducted a survey of coastal ecosystems using the transect method. The socio-economic data of coastal communities were collected using the questionnaire. The biophysical conditions and marine resources were analyzed using descriptive statistical methods. The results showed that the  candidate region has a rich diversity   of coastal ecosystems, but the ecosystem, particularly seagrass beds and coral reefs have been in damaged category. Only the mangrove ecosystem that was still in a good condition category with moderate-to-heavy levels of density. It was discovered 2 regions corresponding to the allotment of the Core Zone, which is in the Region I and III with the total area of 654.22 hectares. For sustainable fisheries zone, Region II and IV would be the first choice with the total area of 620.27 hectares. The Used Zone was identified in the Region V with total area of480.66 hectares. The total area of the region was equal to 1755.15 hectares.